The citizen drone: protest, sousveillance and droneviewing - Zuev, D.; Bratchford, G. (Visual Studies, 2020)
In this article we will discuss the use of drones, as well as the visual simulation of drone afforded aesthetics, by activists, artists and protesters. We use the existing literature of surveillance studies and visual studies to examine how exactly a drone-afforded visibility emerges and how it mediates the visibility of a particular community or space of contention. We draw on the concepts of “surveillance capacities” and (counter) visibility practices to analyse the process and production of drone (and drone-simulated) counter surveillant artist/activist visibility.